2009
DOI: 10.1099/vir.0.011585-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic characterization of hantaviruses from wild rodents and hantavirus pulmonary syndrome cases in the state of Parana (southern Brazil)

Abstract: Over 1100 cases of hantavirus pulmonary syndrome (HPS) have occurred in Brazil since 1993, but little is known about Brazilian hantaviruses, and many of their rodent hosts remain unknown. The Araucaria hantavirus (ARAUV) was described recently from HPS patients from Paraná , in southern Brazil, but its host could not be identified. In this study, rodents were captured from regions with high HPS prevalence to address this issue. ARAUV RNA was detected in three distantly related rodent species: Oligoryzomys nigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
(40 reference statements)
2
28
0
3
Order By: Relevance
“…Hantaviruses can co-circulate in the same locality and can be maintained side-by-side in different rodent species, as reported for Juquitiba and JABV related viruses and other Old World hantaviruses (Artois et al 2007, Chu et al 2009, Raboni et al 2009b, Razzauti et al 2009, Oliveira et al 2011. In this study, we have identified JABV, which is associated with A. montensis and Akodon paranaensis, two related and sympatric rodent species in Midwestern SC (Jabora, 27º09'S 51º47'W).…”
mentioning
confidence: 77%
“…Hantaviruses can co-circulate in the same locality and can be maintained side-by-side in different rodent species, as reported for Juquitiba and JABV related viruses and other Old World hantaviruses (Artois et al 2007, Chu et al 2009, Raboni et al 2009b, Razzauti et al 2009, Oliveira et al 2011. In this study, we have identified JABV, which is associated with A. montensis and Akodon paranaensis, two related and sympatric rodent species in Midwestern SC (Jabora, 27º09'S 51º47'W).…”
mentioning
confidence: 77%
“…The molecular tests were carried out using various sets of primers that have been described previously. 6,7,12 The PCR products were purified (High Pure PCR kit, Roche Inc., Mannheim, Germany) and both strands were sequenced by the commercial Macrogen facility (Seoul, Republic of Korea).…”
Section: Methodsmentioning
confidence: 99%
“…6,7 This region borders Paraguay and Argentina in the West and the states of Santa Catarina (South) and São Paulo (North). Its main economic activities are agriculture, reforestation, and ecotourism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sua distribuição geográfica não é bem conhecida, mas existem registros para Rio de Janeiro (D'Andrea et al 2007), Paraná (Raboni et al 2009) e Santa Catarina (Hershkovitz 1994, Cherem et al 2004.…”
Section: Distribuição Geográfica E Ocorrência Em Biomasunclassified